أثر إدراك العملاء لجودة الخدمات المقدمة على حجم المعاملات المصرفية (دراسة ميدانية على عملاء المصرف العقاري في محافظة اللاذقية) - الحموي فواز صالوم; حمدان مهند رامز (Latakia University Journal - Economic and Legal Sciences Series, 2013)
تلعب الجودة دوراً مهماً في نشاط أي منظمة خدمية وخاصة المصارف، حيث إن عملية تقديم الخدمة المصرفية بدرجة عالية من الجودة أمر على جانب كبير من الأهمية للمصارف، فهي تمكنها من اكتساب ميزة تنافسية وتحقيق الربحية، وزيادة حجم معاملاتها المصرفية وتأمين استمرارها في سوق العمل المصرفي. فالهدف الرئيس لهذا البحث هو: دراسة واقع جودة الخدمات المصرفية المقدمة للعملاء في محافظة اللاذقية، من حيث مفهومها ومحدداتها وأبعادها وقياسها، بالإضافة إلى العلاقة بين مقدم الخدمة (المصرف) وبين المستفيدين منها (عملاء المصارف)، وقد طبق هذا البحث على عينة من عملاء المصرف العقاري، وذلك من خلال قياس إدراك العملاء لجودة الخدمات المصرفية الفعلية وأثرها على حجم المعاملات المصرفية، وقد توصل الباحث إلى مجموعة من التوصيات، وكان أهمها: ضرورة التحديث المستمر للتكنولوجيا المستخدمة في تقديم الخدمات المصرفية، وزيادة الاهتمام بالعملاء وتلقي شكواهم ومقترحاتهم، وزيادة عدد الصرافات لتغطي تجمعات سكنية أكبر. The quality plays an important role on the activity of any service institute especially banks, where the operation of offering banking service in a high degree of quality is necessary for banks, it gives it the possibility of earning a competitive character, achieving profiting, increasing the size of banking transactions and insuring its continuity in the banking job market. The main goal for this research is studying of reality of banking service quality for the customers in Lattakia city as for its concept- characteristics- dimensions and its size, in addition to the relation between the offering service (Bank) and payees from it (Banking Customers). This research was applied on a sample of banking customers and this is from sizing the awareness of customers for the actual services delivered and its effect on the size of banking transactions. The researcher reaches a group of recommendations and the most important are: the necessarily to convoy the technological development in banking services, the increase of attention to customers’ complaints and suggestions , and the increase of the number of ATM to include more residential gatherings.